Geloofsonderskeiding – moontlikhede van ʼn interdissiplinêre reis - Venter, Leon; Jurgens, Hendriks (Nederduitse Gereformeerde Teologiese Tydskrif, 2012)
Discernment – possibilities of an interdisciplinary journey The article challenges the missional church movement to enter into dialogue with the business community on leadership issues. It illustrates how the work of Otto Scharmer helps faith communities to understand discernment. It assumes a new theological epistemology and accepts the movement away from foundationalism. It illustrates how discernment should take place in a new reality with new interdisciplinary dialogue partners.